1996
DOI: 10.1093/infdis/174.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Monoclonal IgA Antibody to Respiratory Syncytial Virus Protects Rhesus Monkeys against Upper and Lower Respiratory Tract Infection

Abstract: Respiratory syncytial virus (RSV), the major cause of lower respiratory tract disease in infants, is thought to infect the upper airways before spreading to the lower respiratory tract. A rhesus monkey model of RSV infection after upper airway inoculation was used to test the protective effect of intranasal treatment with HNK20, a mouse monoclonal IgA antibody against RSV F glycoprotein. HNK20 was administered once daily for 2 days before RSV challenge and 4 days after challenge. Treatment with 0.5 mg/kg HNK20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 21 publications
3
55
0
3
Order By: Relevance
“…Furthermore, because the IgA made by mucosal plasma (8,15). In fact, IgA has long been known to be able to act as a mucosal barrier to infection by preventing attachment of viruses to epithelial cells, and experimental studies in vivo have demonstrated that virusspecific IgA antibodies can protect the host from infection and resolve chronic infection (7,20,25,27,31). Nevertheless, in spite of a considerable literature, the different protective functions of IgA have not been explored in great depth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because the IgA made by mucosal plasma (8,15). In fact, IgA has long been known to be able to act as a mucosal barrier to infection by preventing attachment of viruses to epithelial cells, and experimental studies in vivo have demonstrated that virusspecific IgA antibodies can protect the host from infection and resolve chronic infection (7,20,25,27,31). Nevertheless, in spite of a considerable literature, the different protective functions of IgA have not been explored in great depth.…”
Section: Discussionmentioning
confidence: 99%
“…Some success has nevertheless been achieved by treatment with high titers of passively acquired neutralizing antibody. In the cotton rat, virus replication during a primary infection was reduced (38), and protection against lower respiratory tract infection was observed (39), and administration of a monoclonal anti-RSV immunoglobulin A (IgA) antibody protected rhesus monkeys against upper and lower respiratory tract infection (47). In humans, treatment of high-risk children with high-titer neutralizing antibody preparations against RSV (16) and with a virus-neutralizing anti-F monoclonal antibody (12) has also been very successful.…”
mentioning
confidence: 99%
“…IgA-mediated protection against viruses and bacteria has been demonstrated by administration of hybridoma-derived monoclonal IgA antibodies in mice (5)(6)(7)(8). S-IgA antibodies assembled in plants afford specific protection in humans against oral streptococcal colonization for at least 4 months (9).…”
mentioning
confidence: 99%